The EU community pharmacy market: The density and its influencing factors - Selina Schwaabe (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2025)
Community pharmacies deliver high-quality health care and are responsible for medication safety. The goal of the government is to ensure nationwide, accessible, and affordable medical health-care services provided by pharmacies. Therefore, the per capita density of community pharmacies matters. Overall, the density of community pharmacies fluctuates, with slightly decreasing tendencies in some countries. So far, studies have shown that changes in the system affect prices and density. However, an overview of the development of the density of European community pharmacies and its causes is still missing. This research is important to counteract decreasing density resulting in a lack of professional health care delivered through pharmacies. I focus on liberal versus regulated market structures and the regulation of mail-order of prescription drugs. The density of community pharmacies is increasingly becoming the focus of health-care policies. The supply of nationwide health-care services, especially with regard to recent pandemics, is important. Community pharmacies are not just a counter for prescription drugs. They deliver high-quality health advice and, in some cases, can replace a doctor's visit. Hence, a decline in the density of community pharmacies can affect people's health (care). During my research, I collected data on the number of community pharmacies per 100,000 inhabitants from 27 EU countries from 2000 to 2021. The motivation for this research comes from both a health-care policy and a personal perspective. I grew up in a pharmacist's household and worked at the family's pharmacy. During this time, I learned about the differences in pharmacy market regulations throughout the EU, which led me to question what influences pharmacy density.
Keywords: 360; pharmacies; community pharmacy; health care; mail-order; market regulations